2008
DOI: 10.2140/gt.2008.12.299
|View full text |Cite
|
Sign up to set email alerts
|

Floer homology and surface decompositions

Abstract: Sutured Floer homology, denoted by SFH, is an invariant of balanced sutured manifolds previously defined by the author. In this paper we give a formula that shows how this invariant changes under surface decompositions. In particular, if (M, \gamma)--> (M', \gamma') is a sutured manifold decomposition then SFH(M',\gamma') is a direct summand of SFH(M, \gamma). To prove the decomposition formula we give an algorithm that computes SFH(M,\gamma) from a balanced diagram defining (M,\gamma) that generalizes the alg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
230
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(232 citation statements)
references
References 15 publications
2
230
0
Order By: Relevance
“…I used SFH in [14] to give a more elegant and direct proof of the fact that knot Floer homology detects the genus of a knot. That proof only relies on Gabai's theory of sutured manifolds and the following two results.…”
Section: Introductionmentioning
confidence: 99%
“…I used SFH in [14] to give a more elegant and direct proof of the fact that knot Floer homology detects the genus of a knot. That proof only relies on Gabai's theory of sutured manifolds and the following two results.…”
Section: Introductionmentioning
confidence: 99%
“…The perpendicular two-plane field v ⊥ 0 is trivial on ∂M if and only if (M, γ) is strongly balanced [Ju08,Prop. 3.4].…”
Section: 2mentioning
confidence: 99%
“…Then Juhász showed that SF H(S 3 (R)) is a knot invariant [Ju08]; that is, the top term of knot Floer homology [OS04b,Ra03] is isomorphic to the sutured Floer homology of the complement: SF H(S 3 (R)) ∼ = HF K(K, genus(R)).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations